Optimization of Regeneration Protocol of Rice from Embryo Derived Callus - Kamal, N; Nasuruddin, KM; Haque, MS; Yasmin, S (Progressive Agriculture, 2013)
An efficient and reproducible protocol for in vitro regeneration is required to achieve high frequency transformation from transformed calli. We report here high frequency plant regeneration from mature embryonic calli of two BINA rice cultivars Binasail and Binadhan-4. Embryonic calllus initiated on MS basal medium supplemented with 2 mg/l 2, 4-D. Several media with different combinations of growth regulators were tried. Maximum shoot regeneration frequency (63.33%) was observed in Binadhan-4 on MS medium supplemented with 5 mg/l Kinetin + 0.5 mg/l NAA. Maximum root regeneration frequency (70.00%) was observed in Binadhan-4 on MS medium supplemented with 6 mg/l Kinetin + 0.5 mg/l NAA. Well developed plantlets were hardened and transferred to the glasshouse. DOI: http://dx.doi.org/10.3329/pa.v18i2.17461 Progress. Agric. 18(2): 25 - 33, 2007